Narrative storytelling as mental health support for women experiencing gender-based violence in Afghanistan. (October 2018) - Mannell, Jenevieve; Ahmad, Lida; Ahmad, Ayesha
Abstract: Rationale: Experiencing gender-based violence (GBV) can have serious consequences for women's mental health. However, little is known about how to address the health consequences of GBV against women in high-prevalence settings where GBV is widely accepted as normal. Objective: This study examines the potential for narrative storytelling to support women's mental health and alleviate the suffering caused by GBV in high-prevalence settings. It adopts a symbolic interactionist perspective to explore the perceptions and lived experiences of women living in safe houses for GBV in Afghanistan. Method: In-depth semi-structured interviews were carried out with women ( n = 20) in two Afghanistan safe houses between March and May 2017. The data were analysed both inductively and deductively using thematic network analysis. Results: The findings reveal the stigmatising and traumatic experiences many women have had when telling their stories of GBV in this context. In contrast, storytelling under supportive conditions was perceived to be a highly valuable experience that could help formulate positive social identities and challenge broader social structures. The supportive conditions that contributed to a positive storytelling experience included the presence of a sympathetic non-judgemental listener and a supportive social environment. Conclusions: These findings offer an alternative to biomedical models of mental health support for women experiencing GBV in high-prevalence settings. They raise the importance of tackling broader social changes that challenge patriarchal social structures, and highlight the potential role that narrative storytelling approaches can play in high-prevalence settings like Afghanistan. Highlights: Women experience multiple forms of gendered violence in Afghanistan. Biomedical models of trauma recovery are poorly suited for gendered violence. Storytelling can create new opportunities for psychological healing from violence. To be effective, storytelling requires a supportive social environment and listener. For women to tell stories safely, patriarchal social structures must be addressed.